Pengalaman orang tua mendampingi proses belajar anak berkebutuhan khusus selama belajar dari rumah pada masa COVID-19: Studi fenomenologis - Swandi, Ni Luh Indah Desira; Immanuel, Aria Saloka; Marheni, Adijanti (Jurnal Psikologi Udayana; Vol 9 No 1 (2022)DO - 10.24843/JPU.2022.v09.i01.p06, 2022)
This study aims to understand how parents interpret experiences in assisting children with special needs to learn from home. This research method is phenomenological qualitative with data collection in the form of semi-structured interviews. Interviews were conducted online with three parents of children with special needs obtained by the purposive sampling method. The data obtained were then transcribed and analyzed by Interpretative Phenomenological Analysis (IPA). The results showed that there were several superordinate themes, namely: (1) parents' views on the child's condition, (2) difficulties faced while accompanying children to study, (3) emotional experiences while accompanying children, (4) relationship and social support obtained and expected by parents, (5) worries and future expectation. In this study, parents conveyed their personal experiences and feelings in accompanying children while learning from home. This finding can contribute to the field of educational and clinical psychology as a basis for providing appropriate interventions for parents in assisting children with special needs to learn from home. Keywords: Children with special needs, learning from home, Covid-19, interpretative phenomenological analysis, parents' experience